diff options
author | Camil Staps | 2015-03-17 22:29:26 +0100 |
---|---|---|
committer | Camil Staps | 2015-03-17 22:29:26 +0100 |
commit | 509520ebc8b75075575671dc96dc6ae3733f51a6 (patch) | |
tree | b84b3ceed0b66044f809acc7746c0aea1e63c046 /week6/camil/9.4.2 | |
parent | week 6 done (diff) |
w6 camil
Diffstat (limited to 'week6/camil/9.4.2')
-rw-r--r-- | week6/camil/9.4.2 | 11 |
1 files changed, 11 insertions, 0 deletions
diff --git a/week6/camil/9.4.2 b/week6/camil/9.4.2 new file mode 100644 index 0000000..c23b58e --- /dev/null +++ b/week6/camil/9.4.2 @@ -0,0 +1,11 @@ +9.4.2 - proof by induction over xs + +Induction base: + Suppose xs = []. Then we have: + flatten (map (map f) xs) = flatten (map (map f) []) = flatten [] = [] = map f [] = map f (flatten []) = map f (flatten xs). + +Induction step: + Suppose flatten (map (map f) xs) = map f (flatten xs) for certain xs of finite length. Then we have: + flatten (map (map f) [x:xs]) = flatten [map f x : map (map f) xs] = (map f x) ++ flatten (map (map f) xs) = (map f x) ++ (map f (flatten xs)) =(9.4.1) map f (x ++ (flatten xs)) = map f (flatten [x:xs]). + +By the principle of induction we have now proven that flatten (map (map f) xs) = map f (flatten xs) for any list of finite length xs.
\ No newline at end of file |